GROWTH AND PRODUCTIVITY ANALYSIS OF WOOD (Global Journal of Human-Social Science, 2011)
In the fast changing liberalized global environment where growth and productivity have emerged as the important agents of growth and development present study is an effort to investigate growth pattern and productivity trends of small scale wood and wooden products industry in Punjab The growth of industry has been measured in terms of four variables namely number of units fixed investment direct employment and production Yearly growth rates have been computed to mirror year to-year fluctuations in growth and compound annual growth rates CAGRs have been worked out to find the impact of the policies of liberalized regime on growth of this industry Productivity trends have been sketched in terms of capital intensity capital output ratio and partial factor productivities The study observed that the liberalization has encouraged mechanization and technological up gradation in the wood and wooden products industry in Punjab The policies of liberalized regime have resulted in lower COR and enhancement of factor productivities but at the expense of employment generation
Keywords: DOM; Productivity; Compound annual growth rate; capital Intensity